1999
DOI: 10.1001/archsurg.134.2.144
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Supply of the Sternocleidomastoid Muscle and Its Clinical Implications

Abstract: Background:The knowledge of the exact anatomy of the sternocleidomastoid (SCM) muscle and its nerve and blood supply must be considered a basic prerequisite for its use as a pedicle muscle flap.Objective: To give an exact description of the courses and variability of all vessels supplying the SCM muscle.Design: Anatomic analysis of all arteries supplying the SCM muscle. Setting:The blood supply of the SCM muscle was studied by dissecting bilaterally the anterior regions of the neck of 31 perfusion-fixed human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 24 publications
(38 reference statements)
1
47
0
Order By: Relevance
“…The SCM artery as well as the occipital artery plays a role as a good landmark for the identification of the HN but the origin site of the SCM artery is not always consistent13). Antonius et al and Luis BF et al reported that the blood supply to the SCM muscle can be categorized into 3 parts : upper, middle, and lower8,11). The upper third of the SCM muscle was found to be constantly supplied by branches of the occipital artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCM artery as well as the occipital artery plays a role as a good landmark for the identification of the HN but the origin site of the SCM artery is not always consistent13). Antonius et al and Luis BF et al reported that the blood supply to the SCM muscle can be categorized into 3 parts : upper, middle, and lower8,11). The upper third of the SCM muscle was found to be constantly supplied by branches of the occipital artery.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the SCM artery supplying the middle part of the SCM muscle originated from the lingual artery; it is extremely rare case. Antonius et al reported only one case during 31 necks (61 preparations) dissection11). The lingual artery (LA) is one of the main arteries supplying the tongue and the floor of the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…18 Siemsson et al reported one failure out of 18 splitted clavicular head of SCM used to repair laryngeal and tracheal defects leaving the sternal head 19 and, according to Watkinson JC et al, the fl ap is rarely used now, but it may still have a role to play fi lling small defects in pharynx and oral cavity, and to cover vessels in the compromised neck. 4 According to a blood supply cadaveric study done by Kierner et al, 20 he had a general agreement that the blood supply of the SCM comes from 3 main arteries described in other main studies, 16,21 for the upper third it is supplied mainly by occipital artery which is further divided into 3 categories smaller upper branches representing 87%, and a single well-developed branch on 33 to 39%, this branch goes with the accessory nerve in 19 to 27%, for the middle third blood supply, the study shows some variability, it concluded that about 50% of cases are supplied directly by the external carotid artery, and in 67 to 71% have branches from superior thyroid artery, and in more than 80% of cases, the lower third of the muscle is supplied by suprascapular artery. Tivari considered the occipital artery as the major blood supply, agreed with Larson and Goepfert results.…”
Section: Sternocleidomastoid Flapmentioning
confidence: 99%
“…22,23 According to this simple review of the blood supply of this muscle in the literature, the clinician may increase the success rate of his sternocleidomastoid fl ap, in addition, the fl ap can be extended by releasing the attachment of the muscle on the mastoid, so increasing the arch of rotation, 12 and the point that we want to emphasize here is the fl ap can be extended by this way without compromising the blood supply, and this was based on two points, fi rst, according to the many studies, the main blood supply is the occipital artery and the superior thyroid artery and that the posterior auricular artery is only a minor pedicle. 20 The second point is that both occipital artery and superior thyroid artery emerge from the external carotid artery from anterior medial side ventrally to the muscle, and give many small branches penetrating the muscle somewhere from anterior margin to continue posteriorly. 16,20,21 So, the safest way to elevate the muscle is to start dissecting the muscle with its fascia from posterior margin to anterior protecting the pedicle and the accessory nerve.…”
Section: Sternocleidomastoid Flapmentioning
confidence: 99%
See 1 more Smart Citation